2003
DOI: 10.2134/jeq2003.1508
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Coliform Bacteria in Composted Beef Cattle Feedlot Manure

Abstract: The link between livestock production, manure management, and human health has received much public attention in recent years. Composting is often promoted as a means of sanitizing manure to ensure that pathogenic bacteria are not spread to a wider environment during land application. In a two-year study (1998 and 1999) in southern Alberta, we examined the fate of coliform bacteria during windrow composting of cattle (Bos taurus) manure from feedlot pens bedded with cereal straw or wood chips. Numbers of total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
82
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(100 citation statements)
references
References 24 publications
13
82
2
3
Order By: Relevance
“…Although the elimination of pathogens by composting has been well documented (Deportes et al, 1998;Tiquia et al, 2002;Larney et al, 2003), composting times and temperatures required to achieve elimination or reduction of the number of E. coli vary widely. Turner (2002) demonstrated inactivation of E. coli in farmyard manure, pig feces, and cereal straw already after 2h at 55 o C. In contrast, Lau and Ingham (2001) reported that E. coli could be cultured from bovine manure kept for 19 weeks at 21 o C. In the present study, E. coli could be cultured at every condition tested after up to 120 days, however the non-O157 STEC-stx2-gene strains were not found after 30 days, indicating that competition among the bacteria associated with the temperature seem to be very important aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the elimination of pathogens by composting has been well documented (Deportes et al, 1998;Tiquia et al, 2002;Larney et al, 2003), composting times and temperatures required to achieve elimination or reduction of the number of E. coli vary widely. Turner (2002) demonstrated inactivation of E. coli in farmyard manure, pig feces, and cereal straw already after 2h at 55 o C. In contrast, Lau and Ingham (2001) reported that E. coli could be cultured from bovine manure kept for 19 weeks at 21 o C. In the present study, E. coli could be cultured at every condition tested after up to 120 days, however the non-O157 STEC-stx2-gene strains were not found after 30 days, indicating that competition among the bacteria associated with the temperature seem to be very important aspects.…”
Section: Discussionmentioning
confidence: 99%
“…The principal manner of disinfection during composting is based on time-temperature relationships that destroy pathogens, although antagonistic microorganisms may also play a role in the process (Himathongkham and Riemann, 1999;Larney et al, 2003). The temperature evolution pattern in the composting system can be divided into four different phases: mesophilic, thermophilic, cooling and maturation.…”
Section: Introductionmentioning
confidence: 99%
“…As well as stabilizing nutrients and allowing their more economical transportation, composting is a means of eliminating many of the undesirable features of raw livestock manure including pathogens such as Escherichia coli (Larney et al 2003b …”
Section: Contaminantsmentioning
confidence: 99%
“…However, the value of the disappearance time is highly dependent on the initial inoculum and detection limits, so although this information is useful for comparing treatments, the absolute disappearance time should not be relied on for assessing the sanitary condition of wastes. Larney et al (2003) investigated the effect of composting and found that beef cattle manure composted with either straw or woodchip bedding showed a 6 log cycle reduction in E. coli content (from 7.57 to 1.24 colonyforming units (cfu)/g dry weight (DW) manure) over 14 days. The standard for compost used in Canada is 10 3 cfu/g DW; hence, this treatment was sufficient to achieve good sanitary conditions.…”
Section: Discussionmentioning
confidence: 99%